'Lend me your ears': An analysis of how voice identification evidence is treated in four neighbouring criminal justice systems. (July 2018) - Robson, Jeremy
This article reviews the approaches taken by the courts to the admissibility of voice identification evidence in four jurisdictions: England and Wales, Scotland, Northern Ireland and the Republic of Ireland. Each jurisdiction addresses the question in a different way and each approach is open to criticism. This paper will argue that a contextualised approach to the problem would allow for improvements which would enhance the quality of the evidence and the adjudicative process.